The Effects of Service Quality and Customer Relationship Management on Customers' Loyalty at ICTel - Idha Rizqi Pratiwi; Sumanto, Sumanto; Hartono, Hartono (Cita konsultindo, 2024)
The rapid development of information and communication technology has significantly impacted various sectors, including the industrial sector. But, PT Infrastruktur Cakrawala Telekomunikasi (ICTel) faces challenges in increase and achieving 100% usage among tenants. In fact, this target must be achieved in 2025. This study investigates the effects of service quality and customer relationship management (CRM) on customers’ loyalty at PT Infrastruktur Cakrawala Telekomunikasi (ICTel). The research employs a quantitative methodology, utilizing surveys to collect data from ICTel customers in Kendal Industrial Estate. The data is analyzed using multiple liniear regression with SPSS 20 to determine the effects between the variables. The results indicate that both service quality has significant effect on customers’ loyalty and customer relationship management has no significant effect on customers’ loyalty. The findings suggest to maintain ICTel’s service quality and fostering customer relationship management to get higher customers’ loyalty, providing valuable insights for ICTel and the future researchers as well. Keyword: service quality, customer relationship management, customer loyalty